Endoplasmic reticulum-Mitochondria Coupling in Alzheimer’s Disease - Michela Rossini; Tânia Fernandes; Irene D’Arsiè; Riccardo Filadi (Contact)
Alzheimer's disease (AD) is the most common neurodegenerative disorder of the elderly and no cure is currently available, as the mechanisms leading to neuronal damage and cognitive impairments remain elusive. In the last years, accumulating evidence highlighted early perturbations of the communication between mitochondria and endoplasmic reticulum (ER) in AD models. In this short review, we summarize recent findings linking alterations of ER-mitochondria coupling with typical AD hallmarks.